PRAKTIK KARTEL MASKAPAI PENERBANGAN DI ERA REVOLUSI INDUSTRI 4.0 - M. Alvin Nur Coiroly; Ahmad Munir; Moh Hudi (MIMBAR YUSTITIA, 2020)
Industrial Revolution 4.0 is a new breakthrough in the business world by relying on information and communication technology. The impact of this industrial revolution also occurred in Indonesia. In the aviation industry for example, ticket booking can be directly purchased via mobile phone. The rapid growth of the national aviation industry makes competition between airlines occur ranging from services to ticket prices. This research uses normative research methods, namely using legislation approaches and conceptual approaches on the concept of conspiracy and cartels by analyzing potential cartels against rising airfares. Business competition methods if done healthily will benefit both consumers and businesses / producers, but unfair business competition can give birth to monopolies and cartel practices. Cartels are considered criminal acts accompanied by criminal fines and/or confinement. The Business Competition Supervisory Commission responded to these allegations by conducting an investigation that was previously only within the limits of research, in the process of investigation must look for at least two tools of evidence to advance to the filing stage then proceed to court.